Communication law : practical applications in the digital age - Caristi, Dom; Davie, William R., 1952-; Lee, Laurie Thomas, 1959- (New York, NY : Routledge, 2022)
"This fully revised third edition brings a fresh approach to the fundamentals of mass media and communication law in a presentation that undergraduate students find engaging and accessible. Designed for students of communication that are new to law, this volume presents key principles and emphasizes the impact of timely, landmark cases on today's media world, providing an applied learning experience. This new edition offers expanded coverage of digital media law and social media, a wealth of new case studies, expanded discussions of current political, social, and cultural issues, and new features focused on ethical considerations and on international comparative law. Communication Law serves as a core textbook for undergraduate courses in communication and mass media law. Online resources for instructors, including an Instructor's Manual, Test Bank, and PowerPoint slides, are available at: www.routledge.com/9780367546694"--
Sources of law and systems of justice -- First amendment in principle and practice -- Sedition and censorship -- Forums of freedom -- Libel -- Privacy -- Intellectual property -- Broadcasting & telecommunications -- Digital media law -- Obscenity and indecency -- Advertising law -- Media business law -- Media and courts -- Freedom of access.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Mass media -- Law and legislation -- United States; Freedom of expression -- United States; Textbooks